2019
DOI: 10.3389/fncel.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Influences of Ethanol on Ischemic Stroke: Role of Inflammation

Abstract: Chronic ethanol consumption dose-dependently affects both incidence and prognosis of ischemic stroke. Our goal was to determine whether the influence of chronic ethanol consumption on ischemic stroke is related to an altered inflammatory profile in the brain. Male C57BL/6J mice were divided into six groups and gavage fed with 0.175, 0.35, 0.7, 1.4, 2.8 g/kg/day ethanol or volume-matched water once a day for 8 weeks. Adhesion molecules, microglial activation, neutrophil infiltration, pro- and anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 53 publications
7
51
0
Order By: Relevance
“…Epidemiological studies have found that heavy ethanol consumption increases the morbidity of ischemic stroke and worsens the prognosis of ischemic stroke, whereas mild-moderate ethanol consumption may reduce the morbidity of ischemic stroke and decrease infarct volume and mortality from ischemic stroke [11][12][13][14][15][16] . Consistently, we recently found that ethanol consumption dose-dependently alters cerebral I/R injury in rodents 17 . Increasing evidence indicates that chronic ethanol consumption alters apoptosis and autophagy in many tissues and organs, such as liver, pancreas, heart, and brain [18][19][20][21][22] .…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Epidemiological studies have found that heavy ethanol consumption increases the morbidity of ischemic stroke and worsens the prognosis of ischemic stroke, whereas mild-moderate ethanol consumption may reduce the morbidity of ischemic stroke and decrease infarct volume and mortality from ischemic stroke [11][12][13][14][15][16] . Consistently, we recently found that ethanol consumption dose-dependently alters cerebral I/R injury in rodents 17 . Increasing evidence indicates that chronic ethanol consumption alters apoptosis and autophagy in many tissues and organs, such as liver, pancreas, heart, and brain [18][19][20][21][22] .…”
supporting
confidence: 82%
“…The control group was gavage fed with 10 ml/kg water. At the end of 8 weeks of feeding, blood pressure, heart rate, and fasting blood glucose were measured similarly as described previously 17 . Blood pressure and heart rate were measured using a CODA mouse tail-cuff system (Kent Scientific, Torrington, CT, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identified comorbidities associated with exclusion from thrombolytic therapy are comparable to existing prospective and retrospective studies, such as increasing age associated with worse outcomes [32], female gender corresponding with significantly higher percentages of cardioembolic strokes [33], and severe carotid artery stenosis, which predicts poor outcome [34]. Other identified comorbidities reported in previous studies are diabetes; due to hyperglycemia, which increases the risk of cerebral hemorrhage with rtPA treatment [35], and chronic alcohol use; which increases excitotoxic/ischemic damage, leading to poor outcomes [36].…”
Section: Discussionsupporting
confidence: 69%